Metabolomics and network pharmacology–guided analysis of TNF-α expression by Argemone mexicana (Linn) targeting NF-kB the signalling pathway in cancer cell lines - Kulshrestha, Sunanda; Goel, Anjana; Banerjee, Subhadip; Sharma, Rohit; Khan, Mohammad Rashid; Chen, Kow-Tong (Frontiers in Oncology, 2024)
IntroductionCancer has emerged as one of the leading causes of fatality all over the world. Phytoconstituents are being studied for their synergistic effects, which include disease prevention by altering molecular pathways and immunomodulation without side effects. The present experiment aims to explore the cancer preventive activities of Argemone mexicana Linn leaves extract in skin cancer cell lines (A431) and colon cancer cell lines (COLO 320DM)). In addition, TNF-α expression patterns and NF-kB signaling pathways have been examined.MethodsLC/MS study of Argemone mexicana Linn extracts in various solvents revealed anti-cancerous phytoconstituents. Network pharmacology analysis used Binding DB, STRING, DAVID, and KEGG for data mining to evaluate predicted compounds using functional annotation analysis. Cytoscape 3.2.1 created “neighbourhood approach” and networks. The MNTD of these extracts was tested on L929 fibroblasts. Skin cancer (A431) and colon cancer (COLO 320DM) cell lines were tested for IC50 inhibition. Evaluation of TNF-α and NF-kB expression in cell culture supernatants and homogenates reveals anti-cancerous effects.ResultsLC-MS analysis of extracts predicted the presence of anticancer alkaloids Berberine, Atropine, Argemexicin, and Argemonin. In Network pharmacology analysis, enrichment was linked to the PI3-AKT pathway for both cancer types. MNTD was calculated at 1000μg/ml in L929. The ethanolic extract at 1000μg/ml significantly inhibited skin cancer cell proliferation by 67% and colon cancer cells by 75%. Ethanolic extract significantly reduced TNF-α expression in both cell lines (p<0.001), with the highest inhibition at 1000μg/ml. In TNF-α stimulated cell lines, 1000μg/ml ethanolic extract significantly reduced the regulation of the NF-kB pathway, which plays a role in cancer progression (p<0.001).ConclusionArgemone mexicana Linn. known as ‘swarnkshiri’ in Ayurveda has been reported to be used by the traditional healers for the treatment of psoriasis and its anti-inflammatory and anti-cancerous properties, according to the Indian Medicinal Plant dictionary. In the experiment, the abatement in the expression of inflammatory cytokine TNF-α and inhibition of NF-kB transcription factor activation could be linked with the downregulation of cancer cell proliferation. The study revealed the anticancer activity of Argemone mexicana Linn in the cancer cell lines and paved a pathway for molecular approaches that could be explored more in In vivo studies.